Konstruksi Tes Kemampuan Berpikir Spasial Model Sharpe-Huynh - Muhammad Aliman; Takhiyattul Ulfi; Syahril Lukman; Hujairah Hi Muhammad (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2019)
Not yet known the basic ability of spatial thinking of high school students at the beginning of the meeting. Resulting in geography learning that is done is not in accordance with the needs of students. Valid test instruments are needed to determine students' spatial thinking skills. This study aims to develop a spatial thinking ability test instrument from indicators developed by Sharpe and Huynh. The quantitative descriptive method was used in this study to test the validity, reliability, different items, the level of difficulty, and the correlation between items using ANATES software version 4.0.9. The results of the study showed that as many as 25 items of feasible questions were used to measure the spatial thinking skills of high school students. The ability of spatial thinking possessed by students can be improved and developed by applying geography learning in accordance with the capacity of spatial thinking abilities.